The Idea of Legal Pluralism in Dispute Resolution of Village Head Election in Madura - Eugenia Brandao Da Silva; Asyiqoh, Lin (CV. Pustaka Parawali, 2024)
The purpose of this study is to find a solution to the weakness of the dispute resolution regulation on the results of the village head election, which is considered to have caused ongoing problems due to the existence of a legal vacuum related to the mechanism for fulfilling the rights of the people who are harmed by the determination of the results of the Village Head Election. This research contributes to creating a dispute resolution model for the election of village heads based on local wisdom values in Indonesia. This study uses empirical legal research methods with socio-legal and anthropo-legal approaches. The results of this study reveal that the proposed model, which involves the existence of judicial institutions at the village level that apply informally and are used as a legal tradition of the Madura community, can be a game-changer in resolving disputes over the results of village heads. This method is considered able to resolve Village head election disputes more quickly and peacefully because they are determined by figures who influence the socio-cultural structure of the Madura community. The results of this study can be used as a reference in implementing policies and legal arrangements related to the dispute resolution mechanism for the results of the Village head election, either independently by the village government or by the Pamekasan Regency Government in making Regional Regulations (Perda) related to the settlement of disputes over the results of the Village head election in Pamekasan Regency.